Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan Go-Jek di Kota Palembang - Irwan Septayuda (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
The development of technology changes the selection of public transportation services. Go-Jek is a public transportation service can be booked online through Smartphone. The purpose of this research is to know the Influence of Service Quality and Price on Go-Jek Customer Satisfaction in Palembang City. The sample used in this research are 70 customers who use Go-Jek in Palembang City and sampling using Purposive Sampling. Technique of collecting research data is interview and questioner. The data obtained were analyzed quantitatively using the analytical tools thoseare the validity test, reliability test, the classical assumption test, multiple linear regression, correlation coefficient, determination coefficient and test significance of T test and F test. From the statistical analysis known multiple linear regression, simultaneously quality of service and price have positive and significant effect to customer satisfaction.